Investigations of sequential leaching behaviour of Cu and Zn from coal fly ash and their mobility in environmental conditions - Sočo, Eleonora; Kalembkiewicz, Jan (Journal of hazardous materials, 2007)
The quantitative evaluation of chemical fraction of Cu and Zn in the coal fly ash by methods of five-step sequential extraction was carried out in order to characterize metal mobility in environmental conditions. The research involved (i) water-soluble (pH 7), (ii) acid-soluble (pH 5), (iii) oxide, (iv) difficult reducible and (v) residual metal fractions. It was discovered, that the total extraction of the studied metals from coal fly ash to solutions take place in the following quantities Cu—39.0 mg kg −1 and Zn—89.0 mg kg −1. The investigations of chemical fractions proved that the subject metals occur mainly in coal fly ash as: oxide (Cu—12.0 mg kg −1, Zn—37.0 mg kg −1) and residual (Cu—9.5 mg kg −1, Zn—27.0 mg kg −1) as well as difficult reducible (Cu—16.5 mg kg −1, Zn—22.0 mg kg −1). Low concentrations of metals for water-soluble fraction (Cu < d.l., Zn—0.5 mg kg −1) and acid-soluble fraction (Cu—1.0 mg kg −1, Zn—2.5 mg kg −1) were observed. The fractions of Cu and Zn leachable from the ash in environmental conditions contain: 2.6% (Cu) and 3.4% (Zn) of metal total amount in the coal fly ash. The obtained mobility parameter of Cu and Zn can be applied to estimate the concentration increase of mobile and hardly mobile forms of these metals in soil polluted with the ash.